Tanggung Jawab PPAT terhadap Akta Hak Tanggungan yang dibuat Sebelum Melakukan Pemecahan/Pemisahan Sertipikat Induk - Salmia, Rts Zuhra Wanda; Rosmidah, Rosmidah; Fathni, Indriya; Sarwani, Raden (Wajah Hukum, 2026)
The objective of this research is to analyze the liability of Land Deed Officials (PPAT) concerning mortgage deeds executed prior to the subdivision or separation of the master certificate. In the encumbrance of mortgage rights, it is required that the collateral object be clear, definite, and identifiable both legally and physically through a land title certificate, to ensure balanced protection for both creditors and debtors. The execution of a Deed of Granting Mortgage Rights (APHT) by a PPAT for an object that has not been subdivided or separated from the master certificate may lead to serious legal complications, ranging from the violation of the principle of specialty to the potential nullification of the deed due to non-compliance with formal requirements. This study utilizes a normative legal research method. The first stage involves a normative approach (library research), conducted using primary legal materials and secondary data, including principles, norms, and legal rules established within legislation and other regulations. The second stage applies a case approach analyzing the Denpasar District Court Decision Number 1097/Pdt.G/2020/PN Dps.